2021
DOI: 10.1186/s41983-021-00393-2
|View full text |Cite
|
Sign up to set email alerts
|

Copeptin: a potential blood biomarker for acute ischemic stroke

Abstract: Background Copeptin is a new blood biomarker for acute ischemic stroke which emerged to assist clinicians with decision-making. Serum copeptin can accurately reflect vasopressin concentration, which plays a role in aggravation of inflammatory responses, ions and neurotransmitters dysfunctions. The objective of this work was to investigate the relation between copeptin level as a blood biomarker and the short-term prognosis of acute ischemic stroke after 3 months. The current study included 45 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…They were classified into 4 groups, according to the type of stroke investigated. The first group consisted of twelve studies focusing on the prognostic potential of serum copeptin among ischemic stroke patients [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. The second group included three studies dealing with the predictive ability of circulating copeptin levels following TIA in terms of stroke recurrence, functional outcome and mortality [ 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were classified into 4 groups, according to the type of stroke investigated. The first group consisted of twelve studies focusing on the prognostic potential of serum copeptin among ischemic stroke patients [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. The second group included three studies dealing with the predictive ability of circulating copeptin levels following TIA in terms of stroke recurrence, functional outcome and mortality [ 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that the evaluation of copeptin concentration within a biomarker panel is found to be coupled with greater prognostic potential following stroke than the assessment of a single blood biomarker. Moreover, in a study conducted by Oraby et al [ 32 ] it was found that elevated copeptin levels were strongly correlated with a more severe stroke, as well as poor short-term functional outcome at 3 months. In agreement with aforementioned data, the researchers reported lower plasma copeptin concentrations in the group of patients undergoing thrombolytic therapies compared to those that were not eligible for reperfusion interventions.…”
Section: Discussionmentioning
confidence: 99%
“…AVP stimulates V1a and V2 receptors, which trigger platelet aggregation, vasoconstriction, and water retention. The above process results, are hypovolemic or normovolemic hyponatremia, and low plasma osmolality may occur [ 38 ]. Hyponatremia is a common condition in patients after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research has revealed the role hydration and related hormones play in various metabolic conditions, specifically glycemic control and the onset of type II diabetes mellitus [ 2 ]. An elevated concentration of AVP and its surrogate biomarker, co-peptin, were associated with a higher incidence of cardiocerebral and metabolic diseases [ [3] , [4] , [5] ].…”
Section: Introductionmentioning
confidence: 99%